Overborrowing, Financial Crises and 'Macro-prudential' Policy - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2011)
This paper studies overborrowing, financial crises and macro-prudential policy in an equilibrium model of business cycles and asset prices with collateral constraints. Agents in a decentralized competitive equilibrium do not internalize the negative effects of asset fire-sales on the value of other agents' assets and hence they borrow too much" ex ante, compared with a constrained social planner who internalizes these effects. Average debt and leverage ratios are slightly larger in the competitive equilibrium, but the incidence and magnitude of financial crises are much larger. Excess asset returns, Sharpe ratios and the market price of risk are also much larger. State-contigent taxes on debt and dividends of about 1 and -0.5 percent on average respectively support the planner's allocations as a competitive equilibrium and increase social welfare.